Characterisation of low density lipoprotein subfraction profile and apoe genotype among diabetic patients - Bebakar, Wan Mohamad Wan (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2001)
Diabetes mellitus is a metabolic disorder characterised by chronic hyperglycaemia and dyslipidaemia, which places diabetics at increased risk of cardiovascular disease. We strongly believed that LDL cholesterol (LDLC), triglycerides (TG) and apolipoprotein E (apo E) genotype are closely related in determining this high risk. This study aims to study the effect of LDL subfraction and apo E genotype on diabetic dyslipidaemia. Normal (n=30) and diabetes mellitus type 2 (n=35) subjects who were not on any drug treatment were studied. Lipid biochemical analysis was performed by automated methods using commercial kits. LDL size was determined by transmission electron microscopy. LDLI and LDL2 are large panicles while LDL3, LDL4, and LDL5 are smaller particles and are considered detrimental to health. Apo E genotype was determined by polymerase chain reaction and restric tion fragment length polymorphism.